Lipase production by Aspergillus ibericus using olive mill wastewater - Abrunhosa, Luís (2013)
Olive mill wastewater (OMW) characteristics make it a suitable resource to be used as a microbial culture media to produce value-added compounds, such as enzymes. In this work, the ability of the novel species Aspergillus ibericus to discolor OMW and produce lipase was studied. An initial screening on plates containing an OMW-based agar medium and an emulsified olive oil/rhodamine-B agar medium was employed to select the strain A. ibericus MUM 03.49. Then, experiments in conical flasks with liquid OMW-based media showed that the fungus could growth on undiluted OMW, with a chemical oxygen demand (COD) of 97 ± 2 g/L, and to produce up to 2,927 ± 54 U/L of lipase. When pure OMW was used in the media, the maximum COD and color reduction achieved were 45 and 97 %, respectively. When OMW diluted to 10 % was used, A. ibericus was able to reduce phenolic and aromatic compounds by 37 and 39 %, respectively. Additionally, lipase production was found to be promoted by the addition of mineral nutrients. When the fermentations were scaled up to a 2-L bioreactor, A. ibericus produced up to 8,319 ± 33 U/L of lipase, and the maximum COD and color reduction were 57 and 24 %, respectively.